Estudio sobre la fabricación y las propiedades mecánicas del adobe utilizado como material de construcción en la parroquia Paletillas, cantón Zapotillo - Barreto Panamito, Luis Fernando (2014)
In Paletillas parish of Zapotillo canton, province of Loja, it was carried out the study denominated “Estudio sobre la fabricación y las propiedades mecánicas del adobe utilizado como material de construcción en la parroquia Paletillas, cantón Zapotillo” to gain information about the manufacturing process of the mud-brick “Adobe” such as the dosages used in the elaboration (clay, sand, organic fiber, water), and the resistance to the compression efforts of the mud-brick that is used as a building material by the residents of this area. The objectives of this researching are:  To identify the manufacturing process of the mud-brick used in rural buildings in Paletillas parish,Zapotillo canton.  To establish the resistance, fracture characteristic to the simple compression of the mud-brick.  To elaborate a handbook about the manufacturing process of the mud-brick to be diffused between the stakeholders of this thematic. Also it was hypothesized:  The resistance of the mud-brick to the compression increases in relation to the drying time of 10, 20, 30, and days. In order to identify the manufacturing process of the mud-brick, we toured the neighborhoods of Paletillas parish looking for the places where building mud-bricks are manufactured, they were located the mud-brick factories (bloqueras) and were chosen two mud-brick producers, once they were located and chosen, we proceed to verify the manufacturing process of the mud-brick getting information about: manufacturing process of the mud-brick since the soil selection until the stacking, and the dosage of the materials used in the elaboration of the mud-brick. To determine the resistance fracture characteristic to the compression, a mud sample that was ready for the elaboration of mud-bricks was taken, and with this the specimens that were analyzed in the laboratory were made, to carry out this work were used samples of 12 specimens for each producer, the specimens had to had cylindrical shape with a 15cm diameter and a 30cm height, the simple compression tests were realized having as a variable the drying time, that is to say we realized test at 10, 20, 30, and 40 days, so it was needed 24 specimens, the results obtained after the tests were graphed contrasting values of resistance vs drying time. The test was realized in this way: the specimen was placed in the press, it was verified that the specimen was placed in the center of the press, after that the laboratory worker turns on the press which applies a constant pressure to the upper side of the raw land brick, until it reaches its breaking. At the moment of failure of the mud-brick the machine shows in the screen the total maximum load applied. For the elaboration of the handbook, was taken into consideration the manufacturing process of the mud-brick at Paletillas parish and additionally information was taken from the document “Manual para la construcción de viviendas con Adobe”, corroborating the obtained data with simple field tests expressed in that handbook. Results The mud-brick producers in Paletillas parish were identified; and, it was learned that exists four mud-brick manufacturers in Paletillas parish which nowadays only work on request due to the considerable decrease of the mud-brick demand. The places and people who manufacture mud-bricks were recorded in a database, and using a GPS the geographic coordinates were taken and a map of the mud-brick factories was made. It was expressed the dosage of the materials in a formula Water – Soil – Organic matter in proportions: in volume the water and the soil, and in weight the organic matter. Thus to the producer 1 corresponds 96lts of water to dose 1; and, the 270 lt of soil corresponds to 270/96= 2,8 = 3; and, the 2,2 Kg of organic matter, on the 270 lt of soil corresponds to 2200gr/ 270lt= 8gr of organic matter for each liter of soil; so, the mud-brick dosage formula for the producer 1 will be: 1 : 1 : 8; that is read: 1 liter of water are mixed with 3 liters of soil and 8 grams of organic matter. In the same way, the materials dosage for the producer 2 will be: 1 : 2,3 : 12; that is read: 1 liter of water are mixed with 2,3 liters of soil and 12 grams of organic matter. For the manufacturing process of the mud-bricks, producer 2 uses 24% more water and 34% more organic matter. From the mix used for manufacturing the mud-bricks, for the producer 1 the 33% is water; while, for the producer 2 approximately 43,5% is water. The granulometry assays about the lands used by the producers in the manufacturing of the mud-bricks tell us that the material used by the producer 1 has a 4% more of sand than the material used by the producer 2. The maximum average resistance to the fracture by compression was at the 20 days of drying with a value of 5,9Kg/ cm2 for the producer 1; and, 4,7Kg/ cm2 for the producer 2.